2020
DOI: 10.12688/f1000research.22457.2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the SARS-CoV-2 (2019-nCoV) 3C-like protease (3CLpro) structure: virtual screening reveals velpatasvir, ledipasvir, and other drug repurposing candidates

Abstract: We prepared the three-dimensional model of the SARS-CoV-2 (aka 2019-nCoV) 3C-like protease (3CL ) using the crystal structure of the highly similar (96% identity) ortholog from the SARS-CoV. All residues involved in the catalysis, substrate binding and dimerisation are 100% conserved. Comparison of the polyprotein PP1AB sequences showed 86% identity. The 3C-like cleavage sites on the coronaviral polyproteins are highly conserved. Based on the near-identical substrate specificities and high sequence identities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
198
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(218 citation statements)
references
References 34 publications
4
198
1
2
Order By: Relevance
“…Comparative analysis of the affinity tendency observed for three of the 12 evaluated compounds previously reported by Farag et al (Darunavir > rosuvastatin > saquinavir) [8], Chen et al (ledipasvir > velpatasvir) [9], Adem et al (hesperidin > rutin > diosmin) [35], and Kumar et al (tipranavir > raltegravir) [10] revealed discrepancies when compared with our findings. These observations highlight the degree to which the computational strategy employed to identify potential inhibitors of SARS-CoV M pro impacted affinity tendency, and underscored the utility of combining docking, MD simulations and end-point binding free energy methods.…”
Section: Free Energy Of Bindingcontrasting
confidence: 99%
See 1 more Smart Citation
“…Comparative analysis of the affinity tendency observed for three of the 12 evaluated compounds previously reported by Farag et al (Darunavir > rosuvastatin > saquinavir) [8], Chen et al (ledipasvir > velpatasvir) [9], Adem et al (hesperidin > rutin > diosmin) [35], and Kumar et al (tipranavir > raltegravir) [10] revealed discrepancies when compared with our findings. These observations highlight the degree to which the computational strategy employed to identify potential inhibitors of SARS-CoV M pro impacted affinity tendency, and underscored the utility of combining docking, MD simulations and end-point binding free energy methods.…”
Section: Free Energy Of Bindingcontrasting
confidence: 99%
“…in previous studies that virtually screened candidates targeting monomeric SARS-CoV2 M pro[8][9][10][11]. Of the 12 FDA approved drugs identified, darunavir, indinavir, saquinavir and tipranavir are HIV protease inhibitors, and…”
mentioning
confidence: 99%
“…Accordingly, active genomic surveillance and close monitoring of the genomic sequence dynamics of SARS-CoV-2 is urgently required to: a) trace the pattern of geographic spread of the virus during the ongoing pandemic 10,11 ; b) ensure the effectiveness of vaccines and immune-based diagnostic or therapeutic interventions currently in use or under investigation 9 ; and c) identify putative therapeutic targets. [12][13][14] Geographic, gender, and age discrepancy of COVID-19 disease outcome have been reported by several studies. [15][16][17][18] Whether this correlates to SARS-CoV-2 genomic variation is still unclear.…”
Section: Introductionmentioning
confidence: 94%
“…Coronaviruses genome is a single-stranded positive-sense RNA (+ssRNA) molecule with genomic size ranges between 27-32 kbp which contains at least six open reading frames (ORFs) [11][12][13]. The rst ORFs (ORF1a/b) encodes a polyprotein1a,b (pp1a, pp1b) while other ORFs are located on 3′ end encodes at least four structural proteins: envelop glycoprotein spike (S), responsible for recognizing host cell receptors, Membrane (M) proteins, responsible for shaping the virions, the Envelope (E) proteins, responsible for virions assembly and release and the Nucleocapsid (N) proteins are involved in packaging the RNA genome and in the virions and play roles in pathogenicity as an interferon (IFN) inhibitor [14,15]. In addition to the four main structural proteins, there are structural and accessory proteins that are species-speci c, such as HE protein, 3a/b protein, and 4a/b protein.…”
Section: Introductionmentioning
confidence: 99%